Carbon dots/chitosan modified screen-printed carbon electrodes for the detection of bisphenol A - Mohd Daud, Nor Faezah; Abdullah, Jaafar; Yusof, Nor Azah; Zainal, Putri Nur Syafieqah (Malaysian Analytical Sciences Society (ANALIS), 2022)
Bisphenol A (BPA) is an organic compound in daily plastic products. The compound is primarily transferred from water bottles, food cans liners, and dental fillings into foods and beverages. The BPA is considered an endocrine-disrupting compound related to broad health concerns, such as reproduction problems and the development of various cancers. Consequently, developing a reliable analytical approach to determine BPA levels is urgent. The current study developed an electrochemical sensor from modified screen-printed carbon electrodes (SPCE) with carbon dots-chitosan (CDs-CS) to detect BPA. The CDs-modified SPCE provided a good electrocatalytic application with extraordinary electronic properties and significantly enhanced electrical conductivity. The modified SPCE/CDs-CS sensor was prepared through the drop casting technique. Subsequently, its BPA detection abilities were assessed via differential pulse voltammetry (DPV). In investigating the optimum parameters to elevate the performance of the developed sensors, 1% m/v CS concentration and 1:1 (v/v) CDs to CS ratio were recorded. The obtained CDs-CS/SPCE sensor demonstrated great electrocatalytic features for detecting BPA within the 0.4 and 10 µM concentration range with a sensitivity of 0.46 µA/µM (R² = 0.9911) and 0.37 µM limit of detection (LOD).